Depresi, ansietas dan stres serta hubungannya dengan obesitas pada remaja - Huriatul Masdar; Pragita Ayu Saputri; Dani Rosdiana; Fifia Chandra; Darmawi Darmawi (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2016)
Background: Obesity can occur in all ages, including adolescents. Multiple factors were known related to obesity including psychological factor. Eating excessively could be response toward loneliness, grief or depression. Anxiety can contribute to determining the food intake and nutrient substance, and stress can cause behavioral disorders such as abnormal (excessive) eating behavior that leads to obesity. Objective: The aimed of this research was to know depression, anxiety, and stress and their relationship with obesity in adolescents in Pekanbaru. Method: A cross-sectional research was performed, involving 132 subjects taken from 7 of 14 State Senior High Schools in Pekanbaru, 66 subjects were overweight/obese and 66 subjects were normal. Body mass index per age was used to determine their nutritional status according to Indonesian Ministry of Health Standard 2010 for nutritional status of 5-18 years old children. Depression, anxiety, and stress were measured by using DASS 42 Scale, and categorized only into normal or having depression/anxiety/stress. Data were statistically analyzed by using Chi-Square test with significance level 95%.Results: The results showed 17.4% subjects were categorized depression, 65.2% were anxiety and 34.8% were stress. Statistically analyzed using Fisher test showed that there was significant association between depression with obesity (p=0.003, OR=0,219) and stress with obesity (p=0.044, OR=0,028).Conclusion: Psychological aspects such as depression and stress were related to obesity in State Senior High Schools Students in Pekanbaru